2012
DOI: 10.1002/etc.1857
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and toxicity of metals (copper, zinc, cadmium, and lead) and organic compounds (geraniol and benzo[a]pyrene) in the oribatid miteOppia nitens

Abstract: The oribatid mite Oppia nitens has been suggested as a test species for ecotoxicological assessment of contaminated boreal soils. Knowledge of the ecotoxicity of pollutants of different modes of action to this species is necessary to assess its relative sensitivity in comparison with other invertebrates. The toxicity of four metals and two organic chemicals to O. nitens was evaluated over a 28- or 35-d period. Mite survival, reproduction, and tissue accumulation were assessed at the end of the test. Reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 231 publications
(223 reference statements)
4
36
0
Order By: Relevance
“…Validity criteria [28] were met for control survival (!80%) and reproduction (!100 juveniles) in the collembolan test. Although no standardized protocols are available for the mite test, survival (>70%) and reproduction (>20 juveniles) were within previously published values [19,21] and acceptable limits. In the unspiked treatments, juvenile production of O. nitens increased with increase in moisture level until 60% waterholding capacity, after which it declined again (Supplemental Data, Figure S2).…”
Section: Effect Of Moisture On Zn Availability Uptake and Toxicity supporting
confidence: 68%
See 1 more Smart Citation
“…Validity criteria [28] were met for control survival (!80%) and reproduction (!100 juveniles) in the collembolan test. Although no standardized protocols are available for the mite test, survival (>70%) and reproduction (>20 juveniles) were within previously published values [19,21] and acceptable limits. In the unspiked treatments, juvenile production of O. nitens increased with increase in moisture level until 60% waterholding capacity, after which it declined again (Supplemental Data, Figure S2).…”
Section: Effect Of Moisture On Zn Availability Uptake and Toxicity supporting
confidence: 68%
“…Preparation of organisms for metal analysis was done at the Toxicology Centre, University of Saskatchewan (Saskatoon, Saskatchewan, Canada). The procedures for digestion have been fully described . For every batch of organisms that was digested, a blank was prepared to detect and eliminate possible contamination during the digestion process.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, adults of some oribatid species, such as Nothrus silvestris Nicolet, Rhysotritia duplicata (Grandjean) , and Steganacarus magnus , can survive a 1000 μg/g Cd concentration in soil over 36‐wk and 4‐wk exposure, respectively. Owojori and Siciliano demonstrated that O. nitens accumulated Cd with 75% efficiency after 4‐wk exposure. Handling of high amounts of Cd by oribatids may relate to their fungivorous feeding habits; fungi have been shown to accumulate heavy metals, so oribatids might be naturally selected for efficient metal‐detoxification strategies .…”
Section: Discussionmentioning
confidence: 99%
“…The standardized protocol for the assessment of pollutants on its reproduction was done with a ring test involving several laboratories based on information with 2 chemicals—boric acid and dimethoate —suggesting the need for tests with more chemicals to ascertain its sensitivity relative to other species. Mites are considered to have intermediate sensitivity to pollutants in comparison with other soil invertebrates , but this also depends on the pollutant in question . Therefore, a study evaluating the toxicity of various contaminants and the avoidance response of the predatory mite H. aculeifer is warranted.…”
Section: Introductionmentioning
confidence: 99%